Curriculum and Tourism Development in Guanacaste, Costa Rica: An Analysis of the Technical and Higher Educatio - Esteban Barboza-Núñez (Revista Electrónica Educare)
This paper studies the curricular orientation of technical and higher education focused on tourism in technical and public universities in the province of Guanacaste, Costa Rica. It also contrasts this orientation with the types of tourism development existing in that province. In addition, the article analyzes the existing relationship between the training, the teaching of tourism, the curricular contents at a technical and higher level, and the job possibilities of young people aged 16-25 in the labor market. Moreover, the paper contrasts the contents of tourism programs at a technical and higher level with the social needs of the region. This paper is based on the critical approaches to tourism development in Latin America and the sociocultural consequences on local people. Finally, it suggests some changes in the teaching of tourism in Guanacaste so that more critical and encompassing approaches to the study of the field can become possible.